Evaluación in vitro de sustancias antibacterianas producidas por bacterias aisladas de diferentes organismos marinos - Castillo, Isabel; Lodeiros, César; Núñez, Maximiano; Campos, Isabel (Revista de Biología Tropical, 2001)
Bacteria from several groups of marine organisms were isolated and, using direct antibiograms, identified those that produce antibacterial substances, using a human pathogenic strain of Staphylococcus aureus ATCC6538 as revealing microorganism. Bacteria which produce substances that inhibite S. aureus growth were identified through morphological, physiological and biochemical tests. Out of 290 bacteria, 54 (18.6 %) inhibited the growth of S. aureus, but only 27 survived for identification. Bivalves, sponges and corals were the most represented from which 41.2, 33.3 and 29.7 %, respectively, produced antibacterial substances of the isolated bacteria in each group. The marine species with highest proportions of these bacteria were the hard coral Madracis decactis (62.5 %), the sponges Cliona sp. (57.1 %) and the octocoral Plexaura flexuosa (50.0 %). Out of the 27 strains that produced antibacterial substances, 51.8 % were Aeromonas spp. and 14.8 % Vibrio spp. Marine bacteria that produce antibacterial substances are abundant, most belong in the Vibrionacea group and were isolated mainly from corals and bivalve mollusks.